Accelerating Innovation in the Creation of Biovalue: The Cell and Gene Therapy Catapult. (September 2017) - Gardner, John; Webster, Andrew
The field of regenerative medicine (RM) has considerable therapeutic promise that is proving difficult to realize. As a result, governments have supported the establishment of intermediary agencies to "accelerate" innovation. This article examines in detail one such agency, the United Kingdom's Cell and Gene Therapy Catapult (CGTC). We describe CGTC's role as an accelerator agency and its value narrative, which combines both "health and wealth." Drawing on the notion of sociotechnical imaginaries, we unpack the tensions within this narrative and its instantiation as the CGTC cell therapy infrastructure is built and engages with other agencies, some of which have different priorities and roles to play within the RM field.